# Let $p$ be prime and $(\frac{-3}p)=1$. Prove that $p$ is of the form $p=a^2+3b^2$

Let $p$ be prime and $(\frac{-3}p)=1$, where $(\frac{-3}p)$ is Legendre symbol. Prove that $p$ is of the form $p=a^2+3b^2$.

My progress:

$(\frac{-3}p)=1 \Rightarrow$ $(\frac{-3}p)=(\frac{-1}p)(\frac{3}p)=(-1)^{\frac{p-1}2}(-1)^{\lfloor\frac{p+1}6\rfloor}=1 \Rightarrow$ $\frac{p-1}2+\lfloor\frac{p+1}6\rfloor=2k$
I'm stuck here. This is probably not the way to prove that.

Also tried this way:
$(\frac{-3}p)=1$, thus $-3\equiv x^2\pmod{p} \Rightarrow$ $p|x^2+3 \Rightarrow$ $x^2+3=p\cdot k$
stuck here too.

Any help would be appreciated.

-
Look up Thue's lemma – TheOscillator Feb 22 '14 at 13:06

First part: $$\left(\frac{-3}{p}\right)=1 \text{ if and only if }\; p\equiv{1}\!\!\!\!\pmod{3}.\tag{1}$$ This can be achieved through the Gauss quadratic reciprocity theorem in the most general form, or through the following lines. If $p=3k+1$, by the Cauchy theorem for groups there is an order-3 element in $\mathbb{F}_p^*$, say $\omega$; from $\omega^3=1$ follows $\omega^2+\omega+1\equiv 0\pmod{p}$, hence: $$(2\omega+1)^2 = 4\omega^2+4\omega+1 = 4(\omega^2+\omega+1)-3 = -3,$$ and $-3$ is a quadratic residue $\pmod{p}$. On the other hand, if $-3$ is the square of something $\pmod{p}$, say $-3\equiv a^2\pmod{p}$, then: $$\left(\frac{a-1}{2}\right)^3\equiv\frac{1}{8}(a^3-3a^2+3a-1)\equiv\frac{1}{8}\cdot 8\equiv{1},$$ and $\frac{a-1}{2}$ is an order-3 element in $\mathbb{F}_{p}^*$. From the Lagrange theorem for groups it follows that $3|(p-1)$.

Second part: $$\text{If }p\equiv 1\pmod{3},\qquad p=a^2+3b^2.\tag{2}$$ Since by the first part we know that $-3$ is a quadratic residue $\pmod{p}$, there exists an integer number $c\in[0,p/2]$ such that: $$c^2+3\cdot 1^2 = k\cdot p.\tag{3}$$ The trick is now to set a "finite descent" in order to have $k=1$. Let $d$ the least positive integer such that $c\equiv d\pmod{k}$. Regarding $(3)$ mod $k$, we have: $$d^2+3\cdot 1^2 = k\cdot k_1.\tag{4}$$ Since the generalized Lagrange identity states: $$(A^2+3B^2)(C^2+3D^2)=(AC+3BD)^2 + 3(BC-AD)^2,\tag{5}$$ by multiplying $(3)$ and $(4)$ we get: $$(cd+3)^2 + 3(c-d)^2 = k^2 pk_1.$$ Since $cd+3\equiv c^2+3\equiv 0\pmod{k}$ and $c\equiv d\pmod{k}$, we can rewrite the last line in the following form: $$\left(\frac{cd+3}{k}\right)^2+3\left(\frac{c-d}{k}\right)^2 = k_1\cdot p.\tag{6}$$ Now a careful analysis of the steps involved in the algorithm reveals that $k_1<k$, so the descent is able to reach $k_i=1$, or: $$p = a^2 + 3b^2$$ as wanted.

-
+1 Nice :) Fermat's Descent !! – r9m Feb 22 '14 at 13:23
Interesting. I've seen this method for Fermat's Christmas theorem but didn't expect it would work in general. – barto Feb 22 '14 at 15:04
@barto: A similar proof using descent can be used to prove $a^2+2b^2=p$ iff $p=2$ or $p\equiv 1,3\pmod{8}$. $a^2+5b^2=p$ iff $p\equiv 1,9\pmod{20}$ and $a^2+5b^2=2p$ iff $p\equiv 3,7\pmod{20}$ are similar results. :) – r9m Feb 22 '14 at 15:31
Yes, that's what I was thinking. It also works for proving that $p=4k+3$ is the sum of $4$ squares. I guess it won't work for sums of $3$ squares because there is no nice symmetric identity for products of sums of $3$ squares. – barto Feb 23 '14 at 12:06

$(\frac{p}{3})=(\frac{-3}{p})(\frac{p}{3})=(\frac{-1}{p})(\frac{3}{p})(\frac{p}{3})=(-1)^{\frac{p-1}{2}}(\frac{3}{p})(\frac{p}{3})=(-1)^{\frac{p-1}{2}}(-1)^{\frac{p-1}{2}}(-1)^{\frac{3-1}{2}}=-1$

Hence,$(\frac{-3}{p})=1$ iff, $p\equiv1\mod3$.

Since, there is $x$ such that, $-3\equiv u^2\pmod{p}$

Consider the lattice defined by $L=\{(a,b)\in\mathbb{Z}^2|a\equiv ub\mod p\}$ generated by $(u,1)$ and $(0,p)$.L has index $p$ in $\mathbb{Z}^2$, and area of its fundamental domain is $p$.Now, consider an ellipse $E_n$ deined by $x^2+3y^2=n$, then the area of $E_n=\frac{\pi n}{\sqrt3}>1.8n$

Choose, $n=2.3p$, then Area of $E_{n}>4p$ and $E_n\cap L$ has a non zero point $(a,b)$.

Now, $a^2+3b^2\equiv(ub)^2+3b^2\equiv b^2(u^2+3)\equiv0 \mod p$.

Since, $(a,b)\in E_n \implies a^2+3b^2<2.3p$ we have $a^2+3b^2=p,2p$.

But, $a^2+3b^2=2p \implies a^2\equiv 2p \mod 3 \equiv 2 \mod 3$ contradiction !!

Therefore, $a^2+3b^2=p$.

-
How did you reach your very first equality?? – DonAntonio Feb 22 '14 at 14:17
@DonAntonio : Edited. – r9m Feb 22 '14 at 14:47
Thank you for your answer! giving this one to Jack – Eliran Koren Feb 22 '14 at 15:24